Ответы и объяснения

2014-01-13T21:01:49+04:00
Оформляются, конечно, условия задачи по-другому. Ну ладно, поехали)
1)(\frac{z}{x-z}+ \frac{x+z}{z}): \frac{x}{x^{2}-z^{2}}= (\frac{z^{2}}{(x-z)z}+ \frac{(x+z)(x-z)}{z(x-z)}) \frac{x^{2}-z^{2}}{x}= \frac{(z^{2}+x^{2}-z^{2})}{(x-z)z}* \frac{x^{2}-z^{2}}{x}  \\ = \frac{x^{2}}{(x-z)z}* \frac{(x-z)(x+z)}{x}= \frac{x(x+z)}{z}
2) ( \frac{2}{a} + \frac{a}{2}-2)* \frac{a}{6a-12} =  \frac{4+a^{2}-4a}{2a}*  \frac{a}{6(a-2)} =  \frac{(a-2)^{2}}{2a}* \frac{a}{6(a-2)} =  \frac{a-2}{12}